Facilitation contributes to Mediterranean woody plant diversity but does not shape the diversity–productivity relationship along aridity gradients. Issue 2 (9th March 2016) - Rey, Pedro J.; Alcántara, Julio M.; Manzaneda, Antonio J.; Sánchez‐Lafuente, Alfonso M.
Summary: The diversity–productivity relationship (humped‐back model (HBM)) and the stress‐gradient (SGH) hypotheses may be connected when productivity is limited primarily by aridity. We analytically connect both hypotheses and assess the contribution of facilitation to woody plant richness along the aridity gradient of the Western Mediterranean floristic region. We monitored regeneration niches of woody plants, obtaining rarefied species richness and plant relative interaction indices in 54 forests and scrublands in a 1750‐km geographical range across Spain, Morocco and the Canary Islands. We verified the monotonic increase in facilitation with aridity postulated by SGH and the humped‐shape pattern of species richness expected from HBM, which became manifest after expanding the aridity gradient or crossing vegetation types. Along the gradient, interaction balance turned into facilitation earlier in forest than in scrublands. The effects of aridity and interaction balance on species diversity were additive rather than interdependent. Facilitation is an important driver of woody species richness at macroecological scales because it added up to diversity in most sites, with enhanced contribution with increased stress. The HBM was not shaped by species interactions. Results suggest that facilitation may act in Mediterranean vegetation buffering against critical transitions between states allowing woody plant communities to cope with the rise in aridity expected with global warming.